2019
DOI: 10.3389/fpls.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis in Selected Conifer Trees Pinus nigra Arn. and Abies Hybrids

Abstract: Somatic embryogenesis was achieved in the conifers Pinus nigra Arn. and in the hybrids Abies alba ×A. cephalonica and Abies alba ×A. numidica. For initiation of embryogenic tissue in P. nigra, immature zygotic embryos enclosed in megagametophytes were used. The initiated embryogenic cultures were maintained and proliferated on solid culture medium DCR supplemented with 9 μM 2,4-D and 2.2 μM BA. Microscopic investigations revealed the presence of bipolar early somatic embryos in proliferating tissue. Suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 96 publications
(151 reference statements)
3
33
0
Order By: Relevance
“…The model conifer Norway spruce (Picea abies) successfully produces ET from mature somatic embryos (Bojarczuk et al 2007), but we found that the optimal explant source was the precotyledonary immature zygotic embryo, collected from ~June 20 to ~July 10 (a develop-mental window of approximately two weeks) in eastern Ontario. Work in black pine (Pinus nigra) has demonstrated that the use of immature zygotic embryos enclosed within the intact megagametophytes is effective in producing ET that differentiate into viable somatic embryos for propagation (Salaj et al 2019). Hoopsii megagametophytes containing small embryos collected prior to this window did not produce ET, nor did ovuliferous scales containing mature embryos collected after this window.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model conifer Norway spruce (Picea abies) successfully produces ET from mature somatic embryos (Bojarczuk et al 2007), but we found that the optimal explant source was the precotyledonary immature zygotic embryo, collected from ~June 20 to ~July 10 (a develop-mental window of approximately two weeks) in eastern Ontario. Work in black pine (Pinus nigra) has demonstrated that the use of immature zygotic embryos enclosed within the intact megagametophytes is effective in producing ET that differentiate into viable somatic embryos for propagation (Salaj et al 2019). Hoopsii megagametophytes containing small embryos collected prior to this window did not produce ET, nor did ovuliferous scales containing mature embryos collected after this window.…”
Section: Discussionmentioning
confidence: 99%
“…After three to five weeks on induction culture media, translucent and filamentous tissue emerged from the radicle end of the megagametophyte. Embryo production was characterized by the appearance of embryonal 'heads' (composed of meristematic cells (Salaj et al 2019)) connected by vacuolated 'suspensors' emerging from the polyembryonic cell mass (Fig. 1c).…”
Section: Initiation Of Embryonic Tissuementioning
confidence: 99%
“…The leaf explants of mature J. oxycedrus trees, which were cultivated on modified SH medium with the addition of 1.33 or 2.21 mg L −1 2,4-D or picloram, were used as explants. In most coniferous species, the successful induction of somatic embryogenesis is dependent on the presence of both auxins and cytokinins in the medium [73][74][75]. However, the results showed that in this juniper species, the induction of a callus was possible only in the presence of auxins.…”
Section: Somatic Embryogenesismentioning
confidence: 91%
“…As Salaj et al (2019) found that DCR medium (Gupta and Durzan, 1985) was a better nutrient medium for conifer tree embryo culture. In the present study, DCR medium was used as a basal medium for embryo germination.…”
Section: In Vitro Culture Media and Conditionsmentioning
confidence: 99%